Learn2Earn: Using Mobile Airtime Incentives to Bolster Public Awareness Campaigns - Swaminathan, Saiganesh; Thies, Indrani Medhi; Mehta, Devansh; Cutrell, Ed; Sharma, Amit; Thies, Bill (ACM Conference on Computer-Supported Cooperative Work and Social Computing (CSCW), 2019)
In rural parts of the developing world, spreading awareness about critical issues in health, governance, and other topics is challenging and costly. Traditional media such as print, radio and TV each have limitations and offer little guarantee that new information is absorbed or retained by the target population. This paper describes Learn2Earn, a system that leverages mobile payments to bolster public awareness campaigns in rural India. Users call an Interactive Voice Response (IVR) system, listen to a brief audio tutorial, and take a multiple-choice quiz to check their understanding. People who pass the quiz receive a mobile top-up (about USD 0.14) and have the opportunity to earn additional credits by referring others to the system. We describe a pilot deployment of Learn2Earn in rural India that spread via word-of-mouth to over 15,000 people within seven weeks. Usage was concentrated among young men, many of them students. In a mixed-methods study, we draw upon call logs, electronic surveys, qualitative interviews, and other sources of data to suggest that Learn2Earn could be an effective way to build awareness about important topics.
Best of CSCW honorable mention